Instant polysaccharide-based emulsions: impact of microstructure on lipolysis - Torcello-Gómez, Amelia; Foster, Tim (Royal Society of Chemistry, 2017)
The development of emulsion-based products through optimisation of ingredients, reduction in energy-input during manufacture, while fulfilling healthy attributes, are major objectives within the food industry. Instant emulsions can meet these features, but comprehensive studies are necessary to investigate the effect of the initial formulation on the final microstructure and, in turn, on the in vitro lipolysis, comprising the double aim of this work. The instant emulsion is formed within 1.5–3 min after pouring the aqueous phase into the oil phase which contains a mixture of emulsifier (Tween 20), swelling particles (Sephadex) and thickeners (hydroxypropylmethylcellulose, HPMC, and guar gum, GG) under mild shearing (180 rpm). The creation of oil-in-water emulsions is monitored in situ by viscosity analysis, the final microstructure visualised by microscopy and the release of free fatty acids under simulated intestinal conditions quantified by titration. Increasing the concentration and molecular weight (Mw) of GG leads to smaller emulsion droplets due to increased bulk viscosity upon shearing. This droplet size reduction is magnified when increasing the Mw of HPMC or swelling capacity of viscosifying particles. In addition, in the absence of the emulsifier Tween 20, the sole use of high-Mw HPMC is effective in emulsification due to combined increased bulk viscosity and interfacial activity. Hence, optimisation of the ingredient choice and usage level is possible when designing microstructures. Finally, emulsions with larger droplet size (>20 μm) display a slower rate and lower extent of lipolysis, while finer emulsions (droplet size ≤20 μm) exhibit maximum rate and extent profiles. This correlates with the extent of emulsion destabilisation observed under intestinal conditions.